2017
DOI: 10.1007/s00264-017-3565-4
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis associated with systemic sepsis

Abstract: III Case control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…1,2 Rates of mortality as high as 10-15%, [3][4][5][6][7][8] osteomyelitis in 8%, 8 and a subjective poor outcome in 20-30% of cases have been reported. 3,6,[8][9][10] The true rate of adverse outcomes has remained uncertain as previous studies have had a number of limitations, such as heterogenous inclusion criteria and inconsistent reporting of outcomes. No study has been joint specific and most studies included patients with small joint infection, prior surgery or joint arthroplasty, and outcomes were reported at inconsistent periods of follow up.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Rates of mortality as high as 10-15%, [3][4][5][6][7][8] osteomyelitis in 8%, 8 and a subjective poor outcome in 20-30% of cases have been reported. 3,6,[8][9][10] The true rate of adverse outcomes has remained uncertain as previous studies have had a number of limitations, such as heterogenous inclusion criteria and inconsistent reporting of outcomes. No study has been joint specific and most studies included patients with small joint infection, prior surgery or joint arthroplasty, and outcomes were reported at inconsistent periods of follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al[ 39 ] and Watson et al[ 40 ] concluded that concomitant tenotomy and tenodesis could relieve pain and improve functional outcomes of patients treated with repairable rotator cuff repairs. In contrast, Keong et al[ 41 ] and Pander et al[ 42 ] concluded that the LHB treatments did not positively speed recovery or affect outcomes. Upon comparing the LHB treatments, Godenèche et al[ 43 ] reported that tenodesis renders better outcomes than tenotomy in isolated supraspinatus tears.…”
Section: Discussionmentioning
confidence: 98%
“…Although unusual, septic arthritis with the development of concurrent systemic sepsis has been associated with poor outcomes in terms of infection recurrence and arthritis progression. [11] Debridements of TKA without hardware removal can lead to treatment failure and longer durations of therapy. Antimicrobial treatment regimens are complex and directed by susceptibility data, when available.…”
Section: Discussionmentioning
confidence: 99%